Early microvascular retinal changes in optical coherence tomography angiography in patients with type 1 diabetes mellitus. Issue 8 (16th February 2017) - Simonett, Joseph M.; Scarinci, Fabio; Picconi, Fabiana; Giorno, Paola; De Geronimo, Daniele; Di Renzo, Antonio; Varano, Monica; Frontoni, Simona; Parravano, Mariacristina
Abstract: Purpose: Diabetic retinopathy (DR) can lead to significant vision loss and blindness and has a particularly high prevalence in patients with type 1 diabetes (DM1). In this study, we investigate quantitative differences in optical coherence tomography angiography (OCTA) data between DM1 patients with no or mild signs of retinopathy and non‐diabetic subjects. Methods: Optical coherence tomography angiography (OCTA) imaging was performed on DM1 patients with no or mild nonproliferative diabetic retinopathy and healthy, age‐matched controls. Parafoveal vessel density and foveal avascular zone (FAZ) area in the deep capillary plexus (DCP) and superficial capillary plexus (SCP) were calculated with automated quantification software and compared between patient cohorts. Results: A significant decrease in parafoveal vessel density was seen in the DCP of DM1 patients compared to non‐diabetic controls (57.0 ± 3.3% versus 60.7 ± 2.4%, p < 0.001). There was no significant difference in SCP parafoveal vessel density, DCP FAZ area, or SCP FAZ area between cohorts. Conclusion: M1 patients with no or mild signs of retinopathy have reduced parafoveal vessel density in the DCP on OCTA when compared to non‐diabetic controls. These OCTA findings suggest that parafoveal capillary nonperfusion is an early process in DM1‐related retinal changes and occurs initially at the level of the DCP. Further investigation is needed to understand the prognostic role of these vascular changes.